MicroRNA‐196 Regulates HOX Gene Expression in Human Gluteal Adipose Tissue - Divoux, Adeline; Xie, Hui; Li, Jian‐Liang; Karastergiou, Kalypso; Perera, Ranjan J.; Chang, R. Jeffrey; Fried, Susan K.; Smith, Steven R. (Obesity (Silver Spring, Md.), 2017)
Objective Lower body fat is associated with diminishing cardiometabolic risk. Physiological differences between gluteofemoral and abdominal subcutaneous adipocyte functions are known, but the molecular basis for depot differences in adipocyte function is poorly understood. The objective of this study was to identify depot differences in microRNA (miRNA) expression in human abdominal and gluteofemoral subcutaneous adipose tissues and their implication in gene regulation. Methods Abdominal and gluteofemoral adipose tissue aspirates obtained from 18 participants (9 male and 9 female, age 30 ± 1.5 y, BMI 27.3 ± 1.23 kg/m2) were analyzed for miRNA expression profiles by next‐generation DNA sequencing. The raw reads were mapped to miRBase 17, and differentially expressed miRNAs were confirmed by qRT‐PCR. The hsa‐mimic‐miR196a was transfected into cultured abdominal preadipocytes isolated from five women with obesity. Target gene expression was evaluated by RT‐qPCR. Results Among the 640 miRNAs detected in adipose tissue, miR196a2, miR196a1, miR196b, and miR204 showed a higher expression in the gluteofemoral depot (fold change = 2.7, 2.3, 1.7, and 2.3, respectively) independent of sex. Bioinformatic analyses and human primary preadipocyte transfection with miR196 suggested that the differentially expressed miRNAs could directly or indirectly modulate homeobox (HOX) gene expression. Conclusions The miR196 gene family could play an important role in the regulation of HOX gene expression in subcutaneous adipose tissue and in fat distribution variation.